An overview of the vessels for electrical submarine cable laying. Issue 3 (April 2021) - Yuan, Zhoulong; Bao, Shanjun; Lin, Junfeng; Zhang, Zhigang; Yu, Qiaohao; Liu, Zhen
Abstract: The cable laying vessel is a key factor for the submarine laying routing, insta llation, and layout. The loading and laying capabilities of a submarine cable vessel alw ays determine the speed and costs of corresponding cable construction engineering, wh ich will significantly affect the electricity transmission of the islands, wind farms, and other offshore energy engineering. Therefore, an overview on the recent development of domestic and international cable laying vessels and related construction equipment i s conducted with the summarizations of the development trends. Furthermore, a perspe ctive of the cable laying vessels in the future is also proposed.